2015
DOI: 10.1007/s00228-015-1966-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical outcomes of patients with non-small-cell lung cancer harbouring epidermal growth factor receptor exon 19 or exon 21 mutations after tyrosine kinase inhibitors treatment: a meta-analysis

Abstract: Patients with NSCLC and EGFR exon 19 deletion had a longer PFS, OS and higher response rates after EGFR-TKI therapy compared with exon 21 L858R mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 50 publications
0
54
2
Order By: Relevance
“…The use of epinephrine during CPR has been considered an essential element of pediatric resuscitation for over 50 years (22, 23). Recommendations by the American Heart Association and International Liaison Committee on Resuscitation (20, 21) with regards to use of epinephrine and additional vasoactive medications have been challenged recently as several reports have demonstrated poorer hospital survival and neurologic outcomes in the adult out-of-hospital cardiac arrest population receiving epinephrine (2428). Contrary to the recommended dosing of epinephrine until return of spontaneous circulation (every 3–5 min intervals), nearly one third of respondents in our survey reported limiting epinephrine doses, regardless of CPR duration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of epinephrine during CPR has been considered an essential element of pediatric resuscitation for over 50 years (22, 23). Recommendations by the American Heart Association and International Liaison Committee on Resuscitation (20, 21) with regards to use of epinephrine and additional vasoactive medications have been challenged recently as several reports have demonstrated poorer hospital survival and neurologic outcomes in the adult out-of-hospital cardiac arrest population receiving epinephrine (2428). Contrary to the recommended dosing of epinephrine until return of spontaneous circulation (every 3–5 min intervals), nearly one third of respondents in our survey reported limiting epinephrine doses, regardless of CPR duration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…33 A recent meta-analysis of 4,835 patients enrolled in clinical trials of EGFR TKIs suggested that patients with an exon 19 deletion have a better prognosis (hazard ratio, 0.61; 95% CI, 0.43 to 0.86). 34 Again, this discrepancy may reflect the sample size differences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a report by Sheng et al . 30 suggested that NSCLC patients with EGFR exon 19 deletion had a longer PFS and OS, and a higher response rate after EGFR-TKI therapy compared with those with exon 21 L858R mutation. Therefore, it is very helpful to identify the subtype of EGFR mutation in the clinical treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%